Role of artificial intelligence in human resource management for optimizing employee productivity - Veshne Nupur; Jamnani Jyoti (ITM Web of Conferences)
Artificial intelligence (AI) has significantly transformed various industries, including human resource management, by enhancing efficiency, decision-making, and employee productivity. Recruitments can be modernized by using catboats, predictive analysis helps in offering data-driven insights that can be used to find skill gaps and people management planning. AI’s advancements have made it easy to integrate AI with HRM for increasing efficiency, despite this a lot of ethical concerns, biases, and privacy issue makes it difficult to implement AI completely in the decision-making process. This paper is a bibliometric study focusing on the evolution of AI with HRM to enhance employee productivity and identify key trends and research gaps. This study considered publications for 10 years from 2014 to 2024 through various databases such as Scopus, Web of Science, and IEEE, the study further divides the literature to highlight the most cited authors, countries contributing to the field, and year-wise contribution. The paper focuses on studying the role of AI in various functional areas of HR such as recruitment, performance, and employee productivity. The findings highlight the increasing role of AI across multiple HR practices. This bibliometric investigation offers valuable findings for researchers and practitioners aiming to use AI to enhance HR jobs.